Pulmonary rehabilitation in pulmonary alveolar proteinosis: a case report - Pereira, Grace C.; Rangwala, Zoeb K. (International Journal of Research in Medical Sciences, 2020)
Pulmonary alveolar proteinosis is a rare lung disease in which surfactant accumulates in the alveoli causing impairment of gas exchange, pulmonary circulation, restrictive lung functions, respiratory and muscular dysfunction. Pulmonary rehabilitation is a core aspect in the management of patients with chronic respiratory diseases. However so far there are no documented studies on the effects of pulmonary rehabilitation in pulmonary alveolar proteinosis. Here authors report the case of a 20 year old female diagnosed with pulmonary alveolar proteinosis and having considerable activity limitations. Pulmonary rehabilitation program of 24 weeks was designed for her after a thorough assessment. The 6-minute walk distance (6 MWD), forced vital capacity (FVC), diffusion capacity for carbon monoxide (DLCO), exercise induced desaturation (SPO2) and QOL were evaluated using the SF-36 questionnaire. All parameters were recorded pre, post and at a follow up at 6 months after pulmonary rehabilitation. The 6MWD, FVC, DLCO, exercise induced desaturation and QOL improved considerably after 24 weeks of PR. At a follow up at 6 months all measures expect the FVC remained maintained. The authors thus conclude that Pulmonary Rehabilitation is effective in improving the exercise capacity, lung functions and quality of life in pulmonary alveolar proteinosis.